Circuit Quantum Electrodynamics (cQED) Hybrid Systems for Quanutm Technological Applications: A Theoretical Study - Nongthombam, Roson (My University, 2025)
In this thesis, we study various quantum phenomena and their applications in a hybrid system implemented on a circuit quantum electrodynamics (cQED) platform. cQED explores the interaction between nonlinear superconducting circuits—functioning as artificial atoms—and quantized electromagnetic fields in the microwave-frequency range. The artificial atom in these circuits is realized through a Josephson tunnel junction, formed by a thin insulating barrier at the interface between two superconductors. The non-linear properties of this junction transform the equally spaced energy levels of a simple LC harmonic oscillator into atomic-like energy levels that are unequally spaced. A notable feature of this artificial atom is its ability to tune the frequency of its energy levels by driving it with a microwave field.
Sarma, Amarendra Kumar